Impact of financial crisis on trade, investment and development : regional perspectives (UN New YorkUS, 1999)
Contains the thoughtful analysis and practical suggestions of first-hand witnesses from large and small companies caught up in the 1997 Asian financial crisis, business and investment experts, representatives of the United Nations regional economic commissions and representatives of the governments the world looks to for action.
High-level segment of the forty-fifth session of the Trade and Development Board 22 October 1998